INTEGRATED SKILLS TEACHING: SPEAKING AND LISTENING TOGETHER - Dadaboyeva Fayyoza Khikmatulloyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article examines the pedagogical approach of Integrated Skills Teaching (IST), focusing on the simultaneous instruction of speaking and listening skills in foreign language education. The article discusses practical strategies for implementing IST, presents a case study from a military academic lyceum, and offers recommendations for educators seeking to integrate these skills effectively.